Comparison of Two Open Sources Customer Relationship Management SugarCRM & Vtiger on Usability for Community College - Siti Nur Thazliah, Mohd Thazali (2012)
The purpose of this study is to perform comparison study on usability attribute of Customer Relationship Management (CRM) in a Higher education mainly for Community College. This study focus on two CRMs software–SugarCRM and Vtiger. CRM functionalities are listed down from literature. Usability evaluation of both systems was done by conducting usability test and comparison analysis of both systems was performed. The test users were asked to answer Post Test Questionnaire (PTQ) after using both CRM systems to know their subjective satisfaction. The comparison analysis base on the evaluation result may help as a guideline for Community Colleges while selecting between the two CRM solutions to be implemented in the colleges. The finding is base on Customer Service Officers’ and the full time students’ perspective after using the CRM systems during usability testing. Currently, entire community college in Malaysia has not implement CRM. Hence, with the available time of fourteen weeks, this study was conducted in five Northern Region Community Colleges. Viewing students as main stakeholder provides competitive advantages and enhances the colleges’ ability to attract, retain and serve its customers. The success of an organization is depending on their ability to manage their customers effectively. Due to the need of deploy CRM in one organization, CRM will become more pervasive.